2014
DOI: 10.1002/jctb.4433
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and in situ magnetization of carbon‐decorated lignocellulose fiber for highly efficient removal of methylene blue

Abstract: BACKGROUND: Magnetic adsorption is currently a popular way to remove chemical pollutants from water. The present work reported highly efficient removal of methylene blue (MB) by magnetically retrievable carbon-decorated lignocellulose fiber (mC@LCF). RESULTS: Carbon-decorated lignocellulose fiber (C@LCF) was successfully synthesized via the hydrothermal carbonization process using a low-cost and environment-friendly lignocellulose fiber (LCF) as raw material. Further, the C@LCF was in situ magnetized by simply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The FTIR spectra of BC700 before and after adsorption of DOX and CIP are displayed in Figure S10 . Typical absorption peaks of biochar existed in the spectra of BC700, including 3430 cm −1 (phenolic O–H stretching) (Xu et al, 2011 ), 1620 cm −1 (the stretching vibration of aromatic C = C bonds) (Chen B. et al, 2011 ; Li M. et al, 2015 ), 1390 cm −1 (–COO– symmetric stretching) (Tang et al, 2011 ), and 1090 cm −1 (alkoxy C–O–C bonds) (Zhang et al, 2012 ). A series of peaks at 400–800 cm −1 were formed after the adsorption of DOX and CIP, which were attributed to aromatic –CH stretching vibration, C–C stretch or C–O–H bending of antibiotics (Ahmed et al, 2016 ), suggesting that plenty of antibiotics molecules were adsorbed onto the surface of the biochar.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of BC700 before and after adsorption of DOX and CIP are displayed in Figure S10 . Typical absorption peaks of biochar existed in the spectra of BC700, including 3430 cm −1 (phenolic O–H stretching) (Xu et al, 2011 ), 1620 cm −1 (the stretching vibration of aromatic C = C bonds) (Chen B. et al, 2011 ; Li M. et al, 2015 ), 1390 cm −1 (–COO– symmetric stretching) (Tang et al, 2011 ), and 1090 cm −1 (alkoxy C–O–C bonds) (Zhang et al, 2012 ). A series of peaks at 400–800 cm −1 were formed after the adsorption of DOX and CIP, which were attributed to aromatic –CH stretching vibration, C–C stretch or C–O–H bending of antibiotics (Ahmed et al, 2016 ), suggesting that plenty of antibiotics molecules were adsorbed onto the surface of the biochar.…”
Section: Resultsmentioning
confidence: 99%
“…For pristine RH700, the absorption peak at 3437 cm -1 in the spectrum was assigned to phenolic O-H stretching 54 and the peak at 2923 cm -1 was long linear aliphatic chain (-CH 2 and -CH 3 ). 28,55 The adsorption peak at 1617 cm -1 could be attributed to the stretching vibration of aromatic C = C bonds 28,56 and the peak at 1093 cm -1 represented alkoxy C-O bonds. 57 After adsorption of TC, DC and CF, there were intense peaks at 800-400 cm -1 , which indicated that a large number of antibiotics molecules were adhered to the surface of the biochar.…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…24 With increasing contact time, the percentage uptake of dye removal rate decreased due to limited vacant adsorption sites as the binding sites of sorbent become saturated with dye molecules. 23 Hence, this has turned into a limiting factor for dye uptake. Similar observations were reported in the removal of colored textile wastewater using chitosan and the authors explained that these were due to the competition for active adsorption sites.…”
Section: Effect Of Initial Dye Concentration and Contact Timementioning
confidence: 99%
“…With decreasing pH, there will be more protons available to protonate amino groups of chitosan and this enhance the attraction of negatively charged dye (AY 17) towards the cationic amines. 22,23 However, as chitosan is a type of pH sensitive cellulose biopolymer which will dissolve and formed hydrogel under extreme acidic condition, therefore the effect of pH was not carried out beyond pH 4. And since by using the natural pH of the binary dye solution, an appreciate amount of both dyes could be removed simultane- …”
Section: 2 Surface Characterizationmentioning
confidence: 99%
See 1 more Smart Citation